SToRytelling to Improve Disease outcomes in Gout (STRIDE-GO): a multicenter, randomized controlled trial in African American veterans with gout - Jasvinder A. Singh (BMC, 2021)
Abstract Background Urate-lowering therapy (ULT) adherence is low in gout, and few, if any, effective, low-cost, interventions are available. Our objective was to assess if a culturally appropriate gout-storytelling intervention is superior to an attention control for improving gout outcomes in African-Americans (AAs). Methods In a 1-year, multicenter, randomized controlled trial, AA veterans with gout were randomized to gout-storytelling intervention vs. a stress reduction video (attention control group; 1:1 ratio). The primary outcome was ULT adherence measured with MEMSCap™, an electronic monitoring system that objectively measured ULT medication adherence. Results The 306 male AA veterans with gout who met the eligibility criteria were randomized to the gout-storytelling intervention (n = 152) or stress reduction video (n = 154); 261/306 (85%) completed the 1-year study. The mean age was 64 years, body mass index was 33 kg/m2, and gout disease duration was 3 years. ULT adherence was similar in the intervention vs. control groups: 3 months, 73% versus 70%; 6 months, 69% versus 69%; 9 months, 66% versus 67%; and 12 months, 61% versus 64% (p > 0.05 each). Secondary outcomes (gout flares, serum urate and gout-specific health-related quality of life [HRQOL]) in the intervention versus control groups were similar at all time points except intervention group outcomes were better for the following: (1) number of gout flares at 9 months were fewer, 0.7 versus 1.3 in the previous month (p = 0.03); (2) lower/better scores on two gout specific HRQOL subscales: gout medication side effects at 3 months, 32.8 vs. 39.6 (p = 0.02); and unmet gout treatment need at 3 months, 30.9 vs. 38.2 (p = 0.003), and 6 months, 29.5 vs. 34.5 (p = 0.03), respectively. Conclusions A culturally appropriate gout-storytelling intervention was not superior to attention control for improving gout outcomes in AAs with gout. Trial registration Registered at ClinicalTrials.gov NCT02741700